Social Choice as a Continuous Mapping from IRnâ†’IR: A Group Invariance Approach - Noakes, Lyle; Coram, Alex (Journal of Reviews on Global Economics, 2014)
Social choice is studied by employing a group invariance approach in a way that appears not to have been previously been exploited. This simplifies the problem and the proofs and provides some new insights into the foundations of impossibility results